Conflict management and emotional regulation strategies influence on the perception of Intimate Partner Violence Perpetration - Perez-Dueñas, Carolina; Sánchez-Moral, Joaquín; Checa, Purificación (Psychology, Society & Education, 2023)
During the evolutionary stage of emerging adulthood (people between 18 and 29 years), the appearance of violence among intimate partner relationships seems to be conditioned by conflict management styles and ways of emotional regulation. The main objective is to study the predictive value of conflict management and emotional regulation styles of reappraisal and suppression in the occurrence of different types of violence committed in the couple. The sample consists of 115 people aged between 18 and 25 years, 81.7% women, these variables being assessed by means of self-report measures. The stepwise hierarchical regression analyses show, with respect to positive conflict management styles, that reflection/communication negatively predicts part of the variance of relational violence, threats and physical violence; time and moment searching predicts negatively verbal/emotional violence; and expression affect predicts negatively verbal/emotional violence and threats. The regarding negative conflict management styles, not only avoidance but also accommodation, predict positively part of the variance of verbal/emotional violence. In conclusion, regarding emotional regulation styles, only suppression influences positively on the occurrence of sexual violence. These results could be useful to understand the occurrence of various ways of intimate partner violence as well as to favor the design of preventive programs, by specifically training adaptive ways of conflict resolution besides the appropriate expression of emotions.